Vegetation Composition and Biomass Production in Community Forest in Sikre VDC adjoining Shivapuri National Park, Kathmandu - Pandey, Sudip; Bajracharya, Siddhartha Bajra (Nepal Journal of Science and Technology, 2011)
The present study describes the structural and floral composition of the vegetation of Sikre Village Development Committee (VDC) at Shivapuri National Park. Systematic sampling technique was used to analyze the vegetation of the forest. A quadrat size of 10mx10m was plotted at respective point for tree study and within 5mx5m plots for shrubs and 1mx1m for herbs analysis. The study recorded a total of 18 tree species from 13 families in the forest area. Among the trees, Uttis (Alnus nepalensis D. Don) and Chilaune [Schima wallichii (DC.) Korth.] were the most dominant species. The major shrubs of the forest areas comprised of Yurilo (Hypericum uralum Buch.-Ham. ex D. Don), Chutro (Berberis aristata DC.) and Angeri (Melastoma melabathricum L.). Among the herbs Bhui Amala (Phyllanthus freternus Webster), Unyu [Dryopteris filix-mas (L.) Schott.] and Banmara (Eupatorium adenophorum Spreng.) were dominant ones in forest ground. The aboveground biomass of tree species was found to be 4021.41kg/ha in which Dhalne katus [Castanopsis indica (Roxb.) Miq.] constituted the large percent of biomass of the forest. The estimated resources demand and supply showed the annual deficit of 112.038t/yr and the carbon stock was calculated to be 2.01t/ha. The Shannon Index of diversity was highest for tree (2.33) followed by shrub (2.22) and herb (2.17) respectively. The density of cut stumps and the density of lopping were 184/ha and 216/ha respectively, which showed that the anthropogenic pressure on community forest was prominent. Key words: basal area; biomass; species diversity; systematic sampling DOI: 10.3126/njst.v11i0.4135 Nepal Journal of Science and Technology 11 (2010) 133-138